Design of a planar passive MMID tag antenna. Issue 12 (17th August 2017) - Hotte, David; Siragusa, Romain; Duroc, Yvan; Tedjini, Smail
Abstract : The concept of millimetre‐wave identification (MMID) extends the ultra‐high frequencies radio frequency identification towards a universal frequency band equals to 5 GHz. The study presents the design of a planar passive MMID tag antenna highlighting the requirement specification and the design methodology. Simulation and experimental results are reported which validate the design procedure until a first MMID tag prototype communicating by backscattering.